2018
DOI: 10.1177/0047239518768513
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Digital Technologies in Tertiary Education: Evidence From India

Abstract: The article delineates the existing paradigm of educational technologies in Indian tertiary education institutions. The findings are expected to be useful for tertiary education institutions and policy makers so that they can reorient the existing policies that will be helpful in providing quality education commensurate with industrial needs. The study investigates the adoption of new educational technologies and its impact on students. The empirical findings are based on primary data collected from state and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Based on empirical data collected at public and private universities located in Delhi (India) and its environs, S. Paul and K. Lal conclude that the use of digital technologies contributes to the development of students' creativity, improves their learning abilities, and increases academic performance. The results of their research illustrate students' opinions on the advantages of using digital technologies: "they contribute to a clearer understanding of the material; they are a better illustration of ideas; they provide the opportunity to communicate with students, and ensure that education meets international teaching methods" (Paul, Lal, 2018).…”
Section: Digitalization Benefitsmentioning
confidence: 85%
“…Based on empirical data collected at public and private universities located in Delhi (India) and its environs, S. Paul and K. Lal conclude that the use of digital technologies contributes to the development of students' creativity, improves their learning abilities, and increases academic performance. The results of their research illustrate students' opinions on the advantages of using digital technologies: "they contribute to a clearer understanding of the material; they are a better illustration of ideas; they provide the opportunity to communicate with students, and ensure that education meets international teaching methods" (Paul, Lal, 2018).…”
Section: Digitalization Benefitsmentioning
confidence: 85%
“…This versatility has increased learning opportunities for many students who had previous experience disparities in access to digital technology for learning. Finally, the study by Paul and Lal [25] explored the adoption of new technology in education and its impact on students in and around Delhi, India. The results indicated that there is a positive correlation between the strength of digital technology use in SLP programmes and its effect on knowledge generation, learning confidence and performance amongst students [25].…”
Section: Digital Technologies For Slp Provisioning In the Twenty-firs...mentioning
confidence: 99%
“…Virtual teaching comes with several advantages, from developing creativity and enriching collective activity (Timmis, Munoz-Chereau, 2019;Shraim, 2014;Paul, Lal, 2018;Bojchenko, Smirnova, 2019), to developing leadership and expanding the boundaries of "self-directed learning" (Berry, 2019;(Pac, 2015;Ahmetzhanova, Yur'ev, 2018;Kohtz et al, 2012). On the other hand, the possible disadvantages of online teaching could be the "effect of distraction" (Gupta, Irwin, 2016;Junco, 2015), development of multitasking, information overload, the dependence on gadgets and electronic devices (Kryukova, 2018;Vinichenko et al, 2018), loss of personality skills, deformation of a person's identity, restraint in developing cognitive abilities, devaluation of moral norms (Dobrinskaya, Martynenko, 2019;Manikovskaya, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%